Unveiling the Landscape of System Thinking Modeling Tools Use in Software Engineering - Borges, Júlia de Souza; Lahass, Thiago Felippe Neitzke; Apolinário, Amanda Brito; Santos Júnior, Paulo Sérgio dos; Barcellos, Monalessa P. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de Software, 2024)
Context: Software organizations involve several processes, people, practices, culture, and other factors that affect their behavior. Understanding the organizational environment is crucial for improving processes and products. System Thinking (ST) provides several tools that help in this matter. ST views an organization as a system, comprising elements and interconnections coherently organized in a structure that produces a characteristic set of behaviors. Objective: Given ST’s successful application in different areas of industry and academia, and its potential to address Software Engineering (SE) problems, we decided to investigate how ST modeling tools have been used in SE. Our goal is to provide a panorama of the use of such tools in SE, identify gaps, and shine a light on research opportunities. Method: We carried out a systematic literature mapping, analyzing 700 publications. From these, we identified 10 publications addressing the use of ST modeling tools in SE and conducted an in-depth analysis by investigating the tools that have been used in SE, the ways of and purposes for using these tools, the SE processes that have been supported by them, and the difficulties and benefits that have been perceived when using such tools. Results: ST modeling tools have been employed to tackle SE issues in organizational contexts and to model and analyze the results of SE studies. Project Management and Requirements Engineering have been the most common processes in which these tools have been applied. ST modeling tools have helped get a holistic understanding of complex systems and identify strategies to address problematic behaviors that affect SE outcomes. Causal loop diagrams have been the predominant tool. The lack of necessary knowledge has been a challenge for using the tools. Conclusion: Using ST tools in SE holds promise. Nevertheless, they also suggest that ST modeling tools have been under-explored in this context. Hence, further investigation into their potential for enhancing SE products and processes is warranted.